Changes in the spectral index of the interplanetary plasma turbulence in the period of low solar activity from observations of strongly scintillating source 3C 298 - Glubokova, S.K.; Chashei, I.V.; Tyul'bashev, S.A.; Shishov, V.I. (Advances in Astronomy and Space Physics, 2013)
We present the results of the analysis of temporal power spectra of interplanetary scintillation for the strong radio source 3C 298 observed at 111 MHz with radio telescope BSA LPI in the period near the solar activity minimum. The velocity of the solar wind plasma irregularities and the power exponent of the turbulence spatial spectrum are estimated from the measured temporal scintillation spectra. It is shown that some high frequency ffattening of the temporal scintillation power spectra due to the noise influence can bias the estimates of the source angular size and the spectral index of plasma turbulence. The comparison between the turbulence parameters for the sources 3C 48 and 3C 298 have been carried out. The decrease in the turbulence spectral exponent by transit from the high latitude fast solar wind to the low latitude slow solar wind is found from the 3C 298 data that confirms similar dependence found recently for the 3C 48 data.